2006
DOI: 10.1002/cncr.22375
|View full text |Cite
|
Sign up to set email alerts
|

Second solid cancers after allogeneic hematopoietic stem cell transplantation

Abstract: The specific roles of classical cadherins at key morphogenetic events during development are still not fully understood. As part of a project to study cadherin function during early mammalian development, we generated mice carrying an HA‐epitope tagged Cdh1 (E‐cadherin) cDNA knocked into the Cdh1 locus, similar to the previously described mouse mutants in which we forced Cdh2 (N‐cadherin) expression in the Cdh1 expression domain. As expected and in contrast to Cdh1Cdh2/Cdh2 and Cdh1−/−, our Cdh1HA/HA mutant em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 98 publications
2
59
0
1
Order By: Relevance
“…The reported cumulative incidence of solid cancers following allogeneic SCT ranges from, 1.2% to 1.6% at 5 years, 2.2 to 6.1% at 10 years and from 3.8 to 14.9% at 15 years post transplantation (1,2,4,(20)(21)(22)(23)(24). There is no evidence for any plateau in the incidence rate (4); rather the slope of the curve continues to show a steadily increased incidence with increased follow-up.…”
Section: Solid Tumorsmentioning
confidence: 99%
“…The reported cumulative incidence of solid cancers following allogeneic SCT ranges from, 1.2% to 1.6% at 5 years, 2.2 to 6.1% at 10 years and from 3.8 to 14.9% at 15 years post transplantation (1,2,4,(20)(21)(22)(23)(24). There is no evidence for any plateau in the incidence rate (4); rather the slope of the curve continues to show a steadily increased incidence with increased follow-up.…”
Section: Solid Tumorsmentioning
confidence: 99%
“…22 Moreover, transplant recipients seem to have a higher risk of developing secondary cancers if the stem cells come from a female donor. 23 The patient described in this present case report was diagnosed with primary CML and never received treatment with imatinib. He received allo-HSCT and a conditioning regimen that contained fludarabine, busulfan, cytarabine and cyclophosphamide, which could have increased his risk for subsequent PTLD.…”
Section: Discussionmentioning
confidence: 78%
“…Reported carcinomas include glioblastoma, squamous cell carcinoma (oral-cavity, skin, vulva), melanoma, basal cell carcinoma, ovarian, gastric and renal carcinomas as well as adenocarcinoma of the lung, liver and rectum. [1][2][3][4][5][6] New epithelial malignancies within o6 months are, however, exceptionally rare. Upon our review of the literature only eight such cases were identified: lung (2), stomach (2), renal (1), ovarian (1) and colon (2).…”
mentioning
confidence: 99%
“…Upon our review of the literature only eight such cases were identified: lung (2), stomach (2), renal (1), ovarian (1) and colon (2). [4][5][6][7][8] Second cancers after transplant are usually recipientderived, but there are cases of donor origin. A recent review of donor-derived second malignancies after HSCT reported 11 such cases published, these included cases of invasive breast adenocarcinoma (1), oral squamous cell carcinoma (7), lung squamous cell carcinoma (1), Kaposi's sarcoma (1) and glioblastoma multiforme (1) occurring at an average of 7.9 (range 1-22) years after HSCT.…”
mentioning
confidence: 99%